2007
DOI: 10.1136/adc.2007.120428
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal pressure value using two continuous positive airway pressure devices

Abstract: The aim of the study was to measure the difference between the set continuous positive airway pressure (CPAP) value and the pharyngeal pressure reading during CPAP in premature infants with mild respiratory distress syndrome, using two different devices: hood CPAP and the conventional nasal system. The preliminary results suggest that hood CPAP may produce more stable pharyngeal pressure than the conventional nasal device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Modern CPAP circuits are designed to have no contribution to resistance, and many include a distal pressure monitoring port to ensure target circuit pressure is maintained. However, factors beyond the circuit may contribute to pressure loss, including leak at the nose or mouth, or resistance of the interface 8 9. Given there is a direct relationship between pressure, resistance and flow, the pressure produced by the system can therefore be used as an indication of the system’s intrinsic resistance, or more specifically, that of the nasal interface 10 11.…”
Section: Introductionmentioning
confidence: 99%
“…Modern CPAP circuits are designed to have no contribution to resistance, and many include a distal pressure monitoring port to ensure target circuit pressure is maintained. However, factors beyond the circuit may contribute to pressure loss, including leak at the nose or mouth, or resistance of the interface 8 9. Given there is a direct relationship between pressure, resistance and flow, the pressure produced by the system can therefore be used as an indication of the system’s intrinsic resistance, or more specifically, that of the nasal interface 10 11.…”
Section: Introductionmentioning
confidence: 99%
“…As recently as 2008 an Italian team published a small trial using a hood-and-neck seal instead of 'nasal prongs' to deliver continuous positive airway pressure. 21 This showed that pharyngeal pressure was more stable when a hood-and-neck seal device was used. The only difference between the approach that we had started to use in 1989 and the approach now being studied in Italy is that we used negative pressure round the chest and they are now using positive pressure round the head.…”
Section: The Wider Damage To Researchmentioning
confidence: 97%
“…Calls for further research and development continue to be made, 20 but clinicians in Stoke are still barred from using CNEP even in older children despite the interest in this type of treatment that persists elsewhere. As recently as 2008 an Italian team published a small trial using a hood-and-neck seal instead of ‘nasal prongs’ to deliver continuous positive airway pressure 21 . This showed that pharyngeal pressure was more stable when a hood-and-neck seal device was used.…”
Section: The Wider Damage To Researchmentioning
confidence: 99%
“…It is estimated that an inspired flow of 5 cm H 2 O results in nasal pharyngeal distending pressure of approximately 2-3 cm H 2 O. 4 Many factors, such as air leak, mouth opening and a diameter of IFT, can affect the delivered pressure. An in-depth knowledge of the possible complications are mandatory before using this model.…”
mentioning
confidence: 99%